Refractory fistula of bladder repaired with transurethral cystoscopic injection of N‐butyl‐2‐cyanoacrylate. Issue 1 (7th November 2019) - Mukai, Sakurako; Shinmei, Shunsuke; Muto, Masayuki; Hatayama, Tomoya; Shikuma, Hiroyuki; Miyamoto, Shunsuke; Fujii, Shinsuke; Sadahide, Kousuke; Sekino, Yohei; Hieda, Keisuke; Inoue, Shogo; Hayashi, Tetsutaro; et al.
Abstract : Introduction: Refractory fistulas of the bladder are not rare, but they can rarely be closed naturally. Bladder fistulas can be treated in various ways. We report the case of an old woman who had a refractory fistula of the bladder that was able to be repaired with transurethral cystoscopic injection of N ‐butyl‐2‐cyanoacrylate. Case presentation: For decades after being treated for cervical cancer in 1970s, the woman frequently suffered from fevers. A computed tomography scan showed pelvic abscess at the left side of her bladder, and cystography showed urine leakage at the wall. Thus, we diagnosed her with a pelvic abscess due to a bladder fistula after radiation. Then, we treated her with drainage, antibiotic agents, and N ‐butyl‐2‐cyanoacrylate. After that, she no longer had fevers, and cystography showed no leakage of urine. Conclusion: This result indicates transurethral cystoscopic injection of N ‐butyl‐2‐cyanoacrylate may treat bladder fistulas safely, minimally invasively, and quickly.